Impact of VEGF‐C Gene Polymorphisms and Environmental Factors on Oral Cancer Susceptibility in Taiwan. (23rd August 2013) - Chen, Mu‐Kuan
Abstract : Objectives: Oral cancer, which is the fourth most common male cancer, is associated with environmental carcinogens in Taiwan. Vascular endothelial growth factor (VEGF)‐C, an angiogenic/lymphangiogenic factor with high expression levels in tumor tissues, plays important roles in the development of several malignancies. This study was designed to examine associations of five VEGF‐C gene polymorphisms with the susceptibility to and clinicopathological characteristics of oral squamous cell carcinoma. Methods: Five single‐nucleotide polymorphisms (SNPs) of VEGF‐C were analyzed by a real‐time polymerase chain reaction (PCR) in 470 male patients with oral cancer and 426 cancer‐free controls. Results: In this study, we found that the VEGF‐C rs7664413and rs2046463 polymorphisms were associated with oral‐cancer susceptibility but not with any clinicopathological parameters. The GGACA or GACTG haplotype of five VEGF‐C SNPs (rs3775194, rs11947611, rs1485766, rs7664413, and rs2046463) combined was also related to the risk of oral cancer. Among 611 male smokers, VEGF‐C polymorphism carriers who also chewed betel quid were found to have a 14.5‐24.2‐fold risk of having oral cancer compared to the VEGF‐C wild‐type carrier who did not chew betel quid. Among 461 male betel‐quid chewers, VEGF‐C polymorphism carriers who also smoked had a 2.7‐18.1‐fold risk of having oral cancer compared to those who carried the wild type but did not smoke. Conclusions: Our results suggest that the two SNPs of VEGF‐C (rs7664413andrs2046463) and either of two haplotypes of five SNPs combined have potential predictive significance in oral carcinogenesis. Gene‐environmental interactions among VEGF‐C polymorphisms, smoking, and betel‐quid chewing might alter one's susceptibility to oral cancer.